ICP design methods for driven piles in sands and clays - Jardine, Richard, 1953- (Thomas Telford, 2005)
Aiming to broaden the recommendations, this work provides procedures that can be applied by geotechnical engineers supported by worked examples for sands and clays. It offers guidance on application to a range of pile types, geotechnical profiles and loading conditions, and discusses the methods' theoretical and practical advantages.